Strategi Manajemen Talenta dan Mental Kerja dalam Meningkatkan Kreatifitas Karyawan Milenial di Perumda BPR Sukabumi - Muhammad Fadhlan Nurfadillah; Asep Muhammad Ramdan; Faizal Mulia Z (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The banking sector faces increasing challenges in managing millennial employees who dominate today’s workforce, particularly in maintaining creativity amid performance fluctuations. Perumda BPR Sukabumi has experienced inconsistencies in employee performance and attendance, indicating potential issues related to talent management practices and work mental conditions. This study aims to examine the influence of talent management strategy and work mental condition on the creativity of millennial employees. A quantitative research design with descriptive and associative approaches was employed. Data were collected through a semantic differential scale questionnaire distributed to 35 millennial employees using a saturated sampling technique. The data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression with SPSS software. The results indicate that talent management strategy has a positive and significant effect on employee creativity, particularly through effective recruitment, development, and retention practices. In addition, work mental condition, reflected in balanced workload, manageable mental effort, and controlled psychological stress, also shows a significant positive effect on creativity. These findings suggest that organizations need to integrate strategic talent management with supportive mental work conditions to enhance creative performance among millennial employees.